Meningkatkan Hasil Belajar Siswa Dengan Model Pembelajaran Berbasis Masalah - Yustina Laoli (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The problem examined in this study is the low learning outcomes of science students in the learning process. The purpose of this study is to find out by applying the Problem Based Learning Model will improve student learning outcomes in the subject matter of changing the nature of objects in Class V-A of SD Negeri 070981 Fodo. This research is a Classroom Action Research which consists of two cycles, where each cycle consists of four stages, namely, planning, action, observation, and reflection. Data collection techniques used are tests of student learning outcomes. The results showed that the average score of the pretest before the action was 42.32 where 25% of students who met the standards of learning completeness, after the first cycle was held, the average score was 65.00 with 62.5% had reached the standard of learning completeness and after the action was taken. in cycle II the average value obtained was 80.87 with 95.75% of students who had met the standard of learning completeness. Thus the application of the Detailed Response model in class V-A can increase the average student learning outcomes of students from cycle I to cycle II with an increase of 15.87 points. Keyword: learning outcomes; Problem Based Learning Abstrak: Masalah yang diteliti dalam penelitian ini adalah rendahnya hasil belajar IPA siswa dalam proses pembelajaran. Tujuan penelitian ini adalah untuk mengetahui dengan menerapkan Model Pembelajaran Berbasis Masalah akan meningkatkan hasil belajar siswa pada materi pokok perubahan sifat benda di Kelas V-A SD Negeri 070981 Fodo. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang terdiri dari dua siklus, dimana tiap siklus terdiri dari empat tahap yaitu, perencanaan, tindakan, observasi, dan refleksi. Teknik pengumpulan data yang digunakan adalah tes hasil belajar siswa. Hasil penelitian menunjukkan bahwa skor rata-rata pretes sebelum diadakannya tindakan adalah 42,32 dimana 25% siswa yang memenuhi standar ketuntasan belajar, setelah diadakan siklus I skor rata-rata adalah 65,00 dengan 62.5% telah mencapai standar ketuntasan belajar dan setelah diadakan tindakan pada siklus II nilai rata-rata yang diperoleh menjadi 80,87 dengan 95,75% siswa yang telah memenuhi standar ketuntasan belajar. Dengan demikian penerapan model Respon Terinci di kelas V-A dapat meningkatkan rata-rata hasil belajar IPA siswa dari siklus I ke siklus II dengan peningkatan 15,87 poin. Kata kunci: hasil belajar; Pembelajaran Berbasis Masalah